Accountability of Bankruptcy Bank Debts (Harapan Sentosa Bank Case Towards Bank Indonesia Liquidity Assistance) - Abidin, Fikri Rafi Musyaffa; Noerman, Chiquita Thefirstly; Puspitasari, Syalaisha Amani; Tarina, Dwi Desi Yayi (IHSA Institute, 2023)
Commercial banks are legal subjects because they are one type of companies or corporations. One of the causes of the liquidation of a commercial bank is bankruptcy. One of the banks in liquidation was the case of Harapan Sentosa Bank. Harapan Sentosa Bank is a bank that has received Bank Indonesia Liquidity Assistance worth 3.87 trillion. Currently, Harapan Sentosa Bank has gone bankrupt but still has debts to Bank Indonesia. Therefore, this research will discuss the legal consequences if the debtor's debts are more than the assets after being declared bankrupt and the responsibility of the Harapan Sentosa Bank for Bank Indonesia Liquidity Assistance debts. This research uses a normative juridical research type using a literature study. The author uses a normative juridical type of research, and the research uses a case approach. The analysis technique used in forming the author's journal is a qualitative technique. The results of this research are that the best suggestion is to take this case to the penal code to force all parties involved in this case to be subject to the maximum punishment. Prosecution as a criminal act of corruption, in this case, is also related to technical problems in the process of investigation, prosecution, and verification, which are considered precise by using the Corruption Crime Law compared to the Banking Law for which there are currently no provisions